Dentro do mar tem rio: notas críticas decoloniais à enunciação “religião” - Verdugo, Marcos Vinícius de Souza (2021)
Decoloniality enunciates movements that operate violence in our present time. We seek to present some decolonial critical notes to the enunciation “religion” in order to destabilize the naturalized forms of North Global knowledge. In the First Movement, we present the criticism of naming as a criticism of the coloniality of being, that is, criticism of the ontological and epistemic forms of violence, which enunciate the silencing of the Other. In the Second Movement, we present the critique of the naturalization of the name "religion" as a critique of the coloniality of knowledge, that is, criticism of the forms of symbolic violence and knowledge, which are enunciated by the North Global epistemology. Finally, we wanted to open the way to rethinking the conditions that brought us to the present, the conditions that determined the present to be as it is, and the deviations disclosed to enunciate Pachamama as place that fits all language-world of Mapu